2005
DOI: 10.1037/0022-3514.89.6.978
|View full text |Cite
|
Sign up to set email alerts
|

Defensive pride and consensus: strength in imaginary numbers.

Abstract: Failure (Study 1) and attachment separation thoughts (Study 2) caused exaggerated consensus estimates for personal beliefs about unrelated social issues. This compensatory consensus effect was most pronounced among defensively proud individuals, that is, among those with the combination of high explicit and low implicit self-esteem (Study 1) and the combination of high attachment avoidance and low attachment anxiety (Study 2). In Study 3, another form of defensive pride, narcissism, was associated with exagger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
124
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(131 citation statements)
references
References 121 publications
(210 reference statements)
7
124
0
Order By: Relevance
“…Similar results were also found by McGregor and colleagues where participants reacted to a personal goal confl ict (e.g. thinking of a complex yet unresolved personal dilemma) with an exaggerated perception of social consensus for group-related worldviews, in-group bias, and worldview defence (McGregor, Nail, Marigold, & Kang, 2005 ;McGregor et al, 2001 ). Attachment threats also caused worldview defence among those high in attachment-related anxiety (Hart, Shaver, & Goldenberg, 2005 ) and made participants more susceptible to social infl uence, as conformity with the opinion of others might enhance their chances to be (re-)admitted into a group (Carter-Sowell, Chen, & Williams, 2008 ).…”
Section: Favouritism Of In-groups Over Out-groups As Approach-orientesupporting
confidence: 77%
“…Similar results were also found by McGregor and colleagues where participants reacted to a personal goal confl ict (e.g. thinking of a complex yet unresolved personal dilemma) with an exaggerated perception of social consensus for group-related worldviews, in-group bias, and worldview defence (McGregor, Nail, Marigold, & Kang, 2005 ;McGregor et al, 2001 ). Attachment threats also caused worldview defence among those high in attachment-related anxiety (Hart, Shaver, & Goldenberg, 2005 ) and made participants more susceptible to social infl uence, as conformity with the opinion of others might enhance their chances to be (re-)admitted into a group (Carter-Sowell, Chen, & Williams, 2008 ).…”
Section: Favouritism Of In-groups Over Out-groups As Approach-orientesupporting
confidence: 77%
“…In contrast, while one study has found that priming of conservative values enhanced a conservative shift to MS threat (Jonas et al, 2008, Study 3), numerous studies have found conservative shifts in the absence of any overt priming-that is, priming apart from the inherent nature of the threat itself (Bonanno & Jost, 2006;EchebarriaEchabe & Fernández-Guede, 2006;Jost et al, 2004;Lambert et al, 2009;Landau et al, 2004;McGregor et al, 2005;Nail et al, in press;Thorisdottir & Jost, 2009;Rosenblatt et al, 1989;Sales, 1972;Sales & Friend, 1973Ullrich & Cohrs, 2007. In this context, the reader will recall from our ''Method'' section that the present data were initially collected for the purposes of testing various theories of racial attitudes.…”
Section: Discussionmentioning
confidence: 81%
“…Yet, numerous laboratory experiments have observed conservative shifts that can be attributed to manipulated threats (e.g., Jost et al, 2004;Lambert et al, 2009;Landau et al, 2004;McGregor, Nail, Marigold, & Kang, 2005;Nail et al, in press;Thorisdottir & Jost, 2009;Rosenblatt, Greenberg, Solomon, Pyszczynski, & Lyon, 1989;Sales & Friend, 1973). Thus, considering the weight of the evidence from studies of both (a) real-world, field studies and (b) laboratory experiments employing threat manipulations, it appears that threats do indeed generally cause shifts in a conservative or right-wing direction.…”
Section: Discussionmentioning
confidence: 97%
“…1 In the following, we provide a brief overview of research on epistemic motivation and argue that adopting clear-cut moral beliefs and convictions, in particular, may come to address such general epistemic motives. Further emphasizing the proposed active nature of ME, we propose that the phenomenon is strongly embedded within interpersonal and intragroup processes, such as consensus-seeking (McGregor, Nail, Marigold, & Kang, 2005;Morris et al, 1976), shared belief systems (Hardin & Higgins, 1996;Kruglanski, Pierro, Mannetti, & DeGrada, 2006), interpersonal self-regulation (Rhodewalt & Peterson, 2008), and religious group affiliation (e.g., Pergament, 2002;Silberman, 2005). We then review some related research on political conservatism suggesting that conservatism should be positively correlated with both MA and ME.…”
mentioning
confidence: 94%